High efficient led for white light - Nazarov, Mihail (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)
The highly efficient red-emitting phosphors (Ca1-xSrx)S:Eu and (Ca1-xSrx)Se:Eu , in